Lithium insertion in α′-NaV2O5: Na-pillaring effect on the structural and electrochemical properties. (20th April 2018) - Baddour-Hadjean, R.; Huynh, L.T.N.; Emery, N.; Pereira-Ramos, J.P.
Abstract: Electrochemically formed α′-NaV2 O5 bronze is investigated here as cathode material for rechargeable lithium batteries. We show that the layered structure of this compound, with Na ions located between the V2 O5 layers, allows the reversible insertion of 1 lithium/mole of bronze at an average voltage of 2.1 V vs. Li + /Li. The Li insertion-extraction mechanism in α′-Lix NaV2 O5 is revealed thanks to ex situ XRD and Raman spectroscopy investigations. A narrow one-phase region occurs in the 0 < x ≤ 0.2 composition range while a two-phase mechanism prevails for 0.2 < x < 1. Also, we show that 0.3 additional Li ions can be inserted according to a second solid solution domain, leading to the fully lithiated α′-Li1.3 NaV2 O5 material. The structure of the α′-LiNaV2 O5 is isomorphic to the pristine material. It is remarkable that only limited structural changes are found in the 0 < x ≤ 1.2 lithium composition range, consisting mainly in a 7% increase in the interlayer c parameter. A high structural reversibility is evidenced, which accounts for the remarkable stable capacities achieved whatever the C rate, near 120 mAh g −1 and 60 mAh g −1 at C/10 and 1C, respectively after 60 cycles. The lithium chemical diffusion coefficient DLi, in the range 10 −9 – 10 −10  cm 2  s −1 in the 0.03 ≤ x ≤ 1.1 composition domain, is little affected by the Li concentration. The high mobility revealed for lithium ions is also supported by BVEL analysis, while a significant activation energy for Na-ions migration ascertains their immobility in the α′-NaV2 O5 lattice. These results demonstrate the interest of large interlayer 2D host lattices stabilized by pillaring species such as Na to achieve a stable cycling behavior, a facile guest cation insertion and to promote the ionic diffusion. Highlights: First investigation of lithium insertion mechanism into 2D α-NaV2 O5 . Remarkable stable capacity of 120 mAh g −1 at C/10 available at 2.1 V. Detailed structural picture upon discharge-charge. Limited and highly reversible structural changes. Promoting effect of sodium pillars.